Second wave of COVID-19 and hesitation of vaccination in India - Singh, Amandeep; Kaur, Harleen (International Journal of Research in Medical Sciences, 2021)
Amid the surge of COVID-19 cases in India have already risked its "window of opportunity" period to have ramped up its progressive and determined vaccination program. Today, as the government has the escalating threat of coronavirus variants, it has entered into the second wave, facing an uptick in COVID-19 cases. The vaccination drive-through vital is again running at a slow pace.